Simulation of laser backscattering system for imaging of inhomogeneity/tumor in biological tissues. (April 2017) - Jeeva, J.B.; Singh, Megha
Highlights: Simulation of multiport optical scanning system. Capable of differentiating the embedded inhomogeneities. Characterization of their optical properties. Capable to detect onset of inhomegeneities. Abstract: Background and objectives: The optical characteristics of biological tissues vary in health and diseases. By analysis of photons scattering process by Monte Carlo simulation (MCS) the inhomogeneities in tissues are to be identified and their images reconstructed. Methods: Digital phantoms with goat's heart as a control tissue embedded with inhomogeneities adipose (high scattering) and spleen (high absorption) are simulated. The phantoms considered are – (a) simulation of the developed stage of inhomogeneity by inclusion of adipose and spleen tissues in control and (b) its onset stage by increasing the optical parameters by 10% at fixed locations in control tissue. These phantoms are scanned by simulated system, consisting of nine ports for photon injection and backscattered photons from each port are received by three ports located at 2, 4 and 6 mm from the injecting port, placed in the direction of x -axis. By the data collected from the entire surface, by processing, three grey-scale images are constructed. For localization of inhomogeneities these images are scanned in terms of normalized backscattered intensity (NBI). Results: The images obtained by MCS with 1 million photons, with error minimized, at respective ports, show the presence of inhomogeneities at various depths, which is further supported by the increase or decrease in the NBI compared to that of control for adipose or spleen, respectively. The increase or decrease is more at first port compared to others. The inhomogeneities located at 2 mm below the surface are better identified by the receiving port located at 2 mm on the surface. The same applies to inhomogeneities located at 4 and 6 mm, respectively. Conclusion: The present simulated system not only shows the presence of inhomogeneties at various depths in tissue phantom but also presents their characteristics.